Advances in green processing of seed oils using ultrasound‐assisted extraction: A review. Issue 10 (16th July 2020) - Mushtaq, Anam; Roobab, Ume; Denoya, Gabriela I.; Inam‐Ur‐Raheem, Muhammad; Gullón, Beatriz; Lorenzo, Jose Manuel; Barba, Francisco J.; Zeng, Xin‐An; Wali, Asif; Aadil, Rana Muhammad
Abstract: A growing interest in green bio‐refining technology using ultrasound to extract high‐added value compounds has been observed in the last decades. Therefore, it is of critical importance to consider the impact of the ultrasound technology on the efficiency of oil extraction from seeds as well as on the properties of extracted oils. The cavitation phenomena induced by ultrasound enhance the oil yield as it shatters the primary cell wall of the seeds and makes an easy release of oil. Thus, the higher oil yield is obtained when ultrasound‐assisted extraction (UAE) is used as compared to conventional methods. The properties of UAE oil such as crystallization, free fatty acid content, and oxidative stability are influenced by the ultrasonic time, temperature, intensity, and type of solvent employed during extraction. It can be concluded that UAE is a more efficient technique, which allows the use of alternative green solvents and the production of high‐quality products. Practical applications: It can be concluded that UAE is a more efficient technique, which allows the use of alternative green solvents and the production of high‐quality products. The advantages of ultrasound technology make it a reliable technique for getting high oil extraction yield. Consumers and oil millers both can get benefit from this technique since it allows obtaining oils with improved quality.